Comparative analysis of Facebook informational and educational pages statistics - Adamia, Zoia K.; Onkovуch, Ganna V.; Biletskyi, V. S.; Onkovуch, Artem D. (Publishing House "Universal", 2022)
Recently, the global information and educational space has been constantly and intensively enriched with new phenomena and forms of their presentation that needs to be comprehended and analyzed. The authors of the article have chosen a specific segment of Facebook network and over the past few months we have tracked a small part of this global phenomenon. The first works, which presented the content analysis of individual information and educational Facebook pages, aroused public interest, prompting the authors of the article to conduct their comparative analysis used in the study of related objects and phenomena. It should be noted that all educational pages on Facebook are professionally oriented and serve to develop a professional and medical competence of the interested educational community. In this study, for comparison, the statistical data of two author's different-themed FB pages have been presented: "Медіашкола професора Ганни Онкович" "Media School of Professor Ganna Onkovych" and "Освіта за спеціальністю "Нафтогазова інженерія та технології"" Education by profession "Oil and Gas Engineering and Technology". Each page has statistical data, which are constantly updated automatically. So, a comparative analysis of Facebook informational and educational pages provides opportunities for obtaining versatile information that can be useful in the processes of monitoring and regulating information flows, in particular, professional information.
Keywords: information and educational space; Facebook network; media education technologies; media didactics; media competence; content analysis; comparative analysis; information flow